Frailty Status and Rehabilitation Outcomes Among Older Adults: A Systematic Review - Seidenz, Ericha (Université d'Ottawa / University of Ottawa, 2021)
Background: Frailty has an impact on outcomes in the acute care and in the community setting but there is minimal research that examines frailty in the geriatric rehabilitation setting. Purpose: The purpose of this thesis was to answer the question “What is the association between frailty status and rehabilitation outcomes among older adults?” Methods: A systematic review using the Cochrane Handbook’s guidelines and adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guideline was completed. Four databases were searched as well as grey literature. Screening, extraction, and quality assessments were completed by two reviewers. Data synthesis was completed through vote counting. Results: Twelve studies met the inclusion criteria from which data were extracted. There is a negative association between frailty and discharge functional status, functional change, discharge to home, and a positive association between frailty and length of stay. Conclusion: Further research is needed on this topic to replicate these findings through meta-analyses. Frailty needs to be addressed in the geriatric rehabilitation setting to improve the functional status of frail patients and reduce extended stays in rehabilitation and decrease discharges to a new place of residence.
Keywords: Frailty; Rehabilitation; Older adults